2009
DOI: 10.5325/transportationj.48.4.0007
|View full text |Cite
|
Sign up to set email alerts
|

Freight Transportation Derivatives Contracts: State of the Art and Future Developments

Abstract: In lean and demand-responsive logistics systems, orders need to be delivered rapidly, accurately, and reliably, even under demand uncertainty. Increasing burdens on the industry motivate the introduction of new methods to manage transportation service contracts. One way to hedge transportation capacity and cost volatility is to create derivative contracts. To date, ocean transportation is the only mode of transportation where this type of contract has been applied. The purpose of this article is to provide an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Second, the industry should enhance coordination of capacity planning across all stakeholders (Maloni and Jackson 2007). Emphasis should be placed on balancing stakeholders' conflicting motivations, sharing responsibility and risk of capacity investments (e.g., fee structures, publicprivate partnerships) (Talley 2007), and pursuing new approaches to contracting and pricing (Tsai, Regan, and Saphores 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the industry should enhance coordination of capacity planning across all stakeholders (Maloni and Jackson 2007). Emphasis should be placed on balancing stakeholders' conflicting motivations, sharing responsibility and risk of capacity investments (e.g., fee structures, publicprivate partnerships) (Talley 2007), and pursuing new approaches to contracting and pricing (Tsai, Regan, and Saphores 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We contribute by showing how a shipper can compare contract types before formulating a request for quotation. Tsai, Regan, and Saphores (2008) showed that shipper‐forwarder relationships can be coordinated using a freight transportation derivative contract, where uncertainty is hedged using real options. Brusset and Temme (2005) argued that transportation outsourcing should include a mix of long‐term contract and spot price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, there is no effective financial derivative for container freights, which makes SMIEEs helpless towards fluctuations of container freights. Previous studies indicate that financial derivatives can be used to significantly reduce business costs and financial risks for non-financial enterprises ( Gay et al, 2011 , Ahmed et al, 2018 ) and reduce logistic costs and increase firm value in the shipping industry ( Kavussanos and Visvikis, 2006 , Tsai et al, 2009 ). From a practical perspective, the development of global container freight derivatives is far behind the development of dry bulk cargo and tanker freight derivatives, which is unfavorable to controlling the additional costs caused by the fluctuation of freights.…”
Section: Introductionmentioning
confidence: 99%